Peacemaking potential of Tantric Buddhism in the Russian sociocultural space - Erendzhenova, Yulia Yu. (The New Research of Tuva, 2024)
The article examines the impact of tantric worldview practices on the socio-cultural space of Russia. Based on the analysis of Buddhist texts, it is determined that the essence of tantric practices lies in the realization of the emptiness nature of existence and the attainment of absolute power (Buddhahood) to aid all sentient beings. Following the process of tantric initiation, Buddhists engage in deity yoga, recognize interdependence, and cultivate compassion. The tantric pacifying fire puja of Shiva Jinseg is performed to eliminate various obstacles and promote universal well-being. Tantric consecration rituals for rabne and tantric ritual dances in the awareness of Buddhists initiate the harmonization process of the surrounding space. Tantric deity yoga, as perceived by traditional Russian Buddhists (Kalmyks and Buryats), could have contributed to strengthening their relations with the imperial dynasty of Russia, to which the latter was attributed divine essence and a special spiritual mission. Evidence of the construction of Buddhist stupas and the performance of the Tsam ritual dance attests to the use of peace-building resources of tantric Buddhism in pre-revolutionary Russia. Currently, in Kalmykia, Buryatia, Tuva, and other Russian regions, regular mass tantric initiations are conducted, predominantly for the meditational deity Kalachakra. Pacifying fire pujas are performed, religious objects are consecrated, and ritual dances are executed (Tsam mystery, Vajra Dance, Joyful dances of Kaita). The overarching goal of these practices is associated with the dissemination of ideals of global well-being. Thus, tantric Buddhism can be considered as a “soft power” in contemporary conditions of societal and cultural development.